2019
DOI: 10.2134/jeq2018.04.0169
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nitrogen Leaching in Logged Beetle‐Killed Forests and Implications for Riparian Fuel Reduction

Abstract: Recent extensive forest mortality and subsequent salvage logging may threaten the water supply from headwater catchments in western North America. Land managers confronting current insect outbreaks and projected increases in forest disturbance require information about the potential water quality consequences of these changes. This study is a hillslopescale evaluation of soil N and C leaching in lodgepole pine forests that have experienced 80% overstory tree mortality. I measured extractable inorganic and ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Hence, gains for forested buffers were relatively small when considering the investments for tree planting and fencing. In terms of managing forested buffers, Rhoades (2019) found that riparian harvesting significantly increased dissolved organic C (DOC), total dissolved N, and NO 3 leaching when this harvesting was performed in beetle‐infested stands (where >80% of trees were already dead). However, these postharvest effects were mediated by rapid regeneration of herbaceous vegetation and aspen shoots.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, gains for forested buffers were relatively small when considering the investments for tree planting and fencing. In terms of managing forested buffers, Rhoades (2019) found that riparian harvesting significantly increased dissolved organic C (DOC), total dissolved N, and NO 3 leaching when this harvesting was performed in beetle‐infested stands (where >80% of trees were already dead). However, these postharvest effects were mediated by rapid regeneration of herbaceous vegetation and aspen shoots.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
“…However, the implications of this management prescription on biodiversity require further research. Harvesting management is also important where buffer zone vegetation comprises trees (Dal Ferro et al, 2019; Zak et al, 2019; Rhoades, 2019) or other biomass (Brown et al, 2019). These issues highlight the important role that clear, robust agricultural and environmental policy can play a part in influencing management and determining the effectiveness of riparian buffer zones.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
See 1 more Smart Citation